Influence of weed free periods on the growth, yield and quality of soybean (Glycine max L.) - Nimu, Sadia Ferdausi; Paul, Swapan Kumar; Salam, Md. Abdus; Sarkar, Shubroto Kumar (Fundamental and Applied Agriculture, 2020)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during December 2018 to May 2019 to study the influence of weed free periods on the growth, yield and quality of soybean (Glycine max L.). The experiment was laid out in a randomized complete block design with three replications. The experi- ment comprised three varieties viz. Binasoybean-1, Binasoybean-3 and BARI Soybean-6, and five weed free periods viz. weedy check, weed free up to 20 days after sowing (DAS), weed free up to 40 DAS, weed free up to 60 DAS and weed free throughout the growth period. The BARI Soybean-6 produced the tallest plant (44.75 cm), the highest number of nodules plant−1 (30.17) and dry matter plant−1 (7.37 g) at 80 DAS for the weed free growth period. Similarly, at harvest, BARI Soybean-6 gave the highest plant height (45.99 cm), number of pods plant−1 (24.27), 1000-seed weight (115.20 g), seed yield (1.58 t ha−1), stover yield (1.92 t ha−1), protein content (43.96%) and oil content (18.70%) while Binasoybean-1 showed the lowest results of all parameters. Weed free throughout the growth period produced the highest plant height (47.92 cm), number of branches plant−1 (6.26), number of pods plant−1 (33.04), 1000-seed weight (123.10 g), seed yield (1.82 t ha−1), stover yield (2.15 t ha−1), protein content (44.80%) and oil content (19.47%) whereas the corresponding lowest values were recorded in weedy check. Seed yield increased by 91.58% in weed free throughout the growth period compared to weedy check. In case of interaction, the highest seed yield (1.97 t ha−1), stover yield (2.28 t ha−1) and protein content (45.50%) were observed in BARI Soybean-6 along with weed free throughout the growth period which was at par with BARI Soybean-6 with weed free up to 60 DAS while the lowest values of all parameters were found in Binasoybean-1 with weedy check treatment. In conclusion, BARI Soybean-6 along with weed free up to 60 DAS is the promising combination for soybean cultivation.